Дослідження моделей управління командою у стресових ситуаціях - Малета, В. М. (ХНУРЕ, 2024)
This investigation explores modern team management models in stressful situations, including the CLEAR PACE, GRPI and Tuckman's Group Development Stages models. The research identified the critical importance of effective team management in stressful conditions to ensure business competitiveness. The main factors defining effective team management in stressful situations include anticipated leadership support, shared team vision, creative collective efficiency, social reflexivity, and safety of participation/ As a result of the study, it was determined that the use of appropriate team management models in stressful situations is a key factor in ensuring the success of team activities and achieving their goals in conditions of uncertainty and high stress levels.
Keywords: модель управління; стресова ситуація